Measurement of Cerebral Blood Flow in Chronic Carotid Occlusive Disease: Comparison of Dynamic Susceptibility Contrast Perfusion MR Imaging with Positron Emission Tomography - Mukherjee, Pratik; Kang, Hyunseon Christine; Videen, Tom O.; McKinstry, Robert C.; Powers, William J.; Derdeyn, Colin P. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Our purpose was to evaluate the accuracy of cerebral blood flow (CBF) measurements obtained by using dynamic susceptibility contrast-enhanced MR imaging, including the influence of arterial input function (AIF) selection, compared with those obtained by using [15O]-H2O positron emission tomography (PET) for patients with chronic carotid occlusion.METHODS: MR images and PET scans were obtained of seven patients with unilateral carotid occlusion and were co-registered for region of interest analysis. PET CBF maps were generated by using the autoradiographic method. MR imaging CBF maps were calculated by deconvolution of the susceptibility time curve with a proximal middle cerebral artery AIF and were converted to absolute flow rates either by assuming a constant contralateral white matter CBF value of 22 mL/100 mL/min or by using individually determined PET white matter CBF values.RESULTS: Although CBF values measured by PET and MR imaging were positively correlated for every patient, the slopes and y intercepts of the regression lines varied widely among patients. The correlation was better when individual white matter CBF values measured by PET were used to scale the white matter CBF values measured by MR imaging (r = 0.84, P < .0001) than when constant contralateral CBF values were assumed (r = 0.54, P < .0001). The choice of AIF ipsilateral or contralateral to the occluded carotid artery made no statistically significant difference (P > .05) to the correlation coefficient, slope, or y intercept of the MR imaging versus PET CBF regressions for six of the seven patients.CONCLUSION: Although linearly correlated with CBF values measured by PET, dynamic susceptibility contrast-enhanced MR imaging was not accurate for measuring absolute CBF values. AIF selection relative to the side of carotid occlusion did not significantly affect calculated MR imaging CBF values for six of the seven patients.